Honda PCX Motorcycle Promotion Consumer Satisfaction - Ismunandar Ismunandar; Chevy Herli Sumerli A; Dian Indah Sari; Slamet Maryoso; Muhammad Yusuf (IAIN Palopo, 2023)
The study aims to analyze the relationship between the promotion of the Honda PCX Motorcycle and consumer satisfaction levels. The Honda PCX Motorcycle is one of the popular models of motorcycles marketed by the Honda Motor Company. Effective promotions can affect consumer perceptions of products and help in influencing their purchasing decisions. Research results show that the promotion of the Honda PCX Motorcycle has a significant impact on consumer satisfaction. Consumers who have a high level of exposure to promotions tend to have a higher level of satisfaction with the product. Effective promotion is able to create higher awareness, build a positive image, and provide relevant information to potential consumers, which in turn increases their satisfaction. The findings have significant implications for Honda Motor Company and other motorcycle manufacturers. They can use these findings to develop more effective promotion strategies and focus on the aspects that most affect consumer satisfaction. Thus, it can be expected that the level of consumer satisfaction will increase, which will ultimately have a positive impact on sales performance and brand reputation.